Republic of Slovenia : 2012 Article IV Consultation-Staff Report; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Slovenia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2012)
Slovenia, among other euro area countries, experienced the largest economic contraction since 2008. The performance of Slovenian banks deteriorated markedly in recent years as a result of the unfavorable operating environment and weak governance. Despite some deleveraging, banks continued to depend heavily on wholesale funding from abroad. Slovenia's rebalancing required relying on supply-side policies, in particular, the labor market. With the banking system under pressure and the corporate sector highly leveraged, the Executive Board recommended strengthening the regulatory and supervisory frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet